Compressible expansion aerogel as well as preparation method and application thereof
By using sodium carboxymethylcellulose and needle pulp to prepare aerogels, the three-dimensional porous structure is constructed through multiple cross-linking, which solves the problems of low overall strength and high preparation cost of existing aerogel materials, and achieves high strength and toughness and good liquid absorption performance.
Patent Information
- Application Number
- CN202411852880.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-18
AI Technical Summary
The existing compressible and expandable aerogel liquid absorbing materials have low overall strength, high production cost, and the materials are easily damaged during actual use.
Using sodium carboxymethylcellulose and needle pulp as raw materials, freeze-drying by adding protic acid, chemical crosslinking agent and sodium dodecyl sulfate solution to construct a multiple crosslinking system to form a three-dimensional porous aerogel .
The high overall strength, toughness and good compression and rebound performance of the aerogel are achieved, reducing the preparation cost and providing greater space for liquid absorption and storage.
Smart Images

Figure CN119463279A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of aerogel materials, and in particular to a compressible expandable aerogel and a preparation method and application thereof. Background Art
[0002] Aerogel refers to a nano-scale porous solid material formed by chemical or physical cross-linking through the sol-gel method to form a three-dimensional network structure that is insoluble in water, and then a certain drying method is used to replace the liquid phase in the gel with gas. Aerogel has expansion, thixotropic and slurry-release effects. At the same time, it also has the characteristics of high porosity and low density. It has been widely used in the fields of biomaterials, adsorption materials, electronic materials, etc. At present, the preparation of high-strength compressible and expandable aerogel liquid-absorbing materials is a major research hotspot in the field of aerogel functional materials.
[0003] Existing compressible and expandable aerogel absorbent materials mainly include carbonized aerogel absorbent materials, gelatin fiber sponge aerogel absorbent materials, carboxymethyl chitosan aerogel absorbent materials, layered nanofiber aerogel absorbent materials, starch-polyethylene glycol aerogel absorbent materials, etc. However, the above materials generally have the problem of low overall strength, and the material itself is easily damaged during actual use, which has an adverse effect on the subsequent use process. At the same time, the above materials, such as the carboxymethyl chitosan raw material cost required for the carboxymethyl chitosan aerogel absorbent material, are relatively high, which is not conducive to large-scale batch production; the nanofiber manufacturing process required for the layered nanofiber aerogel absorbent material is complicated, and the preparation process first needs to synthesize elastic microstructure nanofibers. The preparation of this raw material usually requires electrospinning processing, which has a long preparation cycle, high processing difficulty, low yield, and high production cost. Therefore, it is necessary to provide an aerogel material with low preparation cost, high overall strength, high toughness, and good compression and rebound properties. Summary of the invention
[0004] In view of the problems of high preparation cost, low overall strength and resilience of aerogel liquid-absorbing materials in the prior art, the present invention provides a compressible expandable aerogel and a preparation method and application thereof.
[0005] In order to solve the above technical problems, the technical solution provided by the present invention is:
[0006] A method for preparing a compressible expandable aerogel comprises the following steps:
[0007] S1, adding sodium carboxymethyl cellulose and conifer pulp into water and mixing them evenly to obtain a mixed solution;
[0008] S2, adding protonic acid, chemical crosslinking agent and sodium dodecyl sulfate solution to the mixed solution, mixing evenly, and freezing to obtain a hydrogel; wherein the freezing is performed at a temperature below -15°C for more than 24 hours or at a temperature below -196°C in liquid nitrogen for more than 2 hours;
[0009] S3, washing the hydrogel in water, and drying the hydrogel to obtain a compressible and expandable aerogel.
[0010] Water-soluble polymers are an important class of polymer compounds and have been widely used as sol polymers. However, aerogels prepared using water-soluble polymers as raw materials generally have the defect of low overall strength, which greatly limits their application scope and application environment.
[0011] Compared with the prior art, the preparation method of the compressible expandable aerogel provided by the present invention uses water-soluble polymer sodium carboxymethyl cellulose and coniferous pulp with high strength and modulus as raw materials, and constructs hydrogen bonds and covalent bonds by adding a cross-linking agent to make sodium carboxymethyl cellulose and coniferous pulp fibers fully cross-linked, and uses a method combining a foaming agent and an ice template method to form a three-dimensional porous structure of the aerogel. Among them, the basic structure of the aerogel is built by fully cross-linking between water-soluble polymers, and a denser, thicker and stronger reinforced pore wall structure is obtained by cross-linking between water-soluble polymers and coniferous pulp fibers. The connection between the pore walls of each hole is further strengthened by fully cross-linking between coniferous pulp fibers, and the conduction of force between the pore walls is strengthened. Through the construction of a multiple cross-linking system, high overall strength and strong toughness are finally obtained, while also having good compression performance and expansion performance that rebounds when exposed to water, and the three-dimensional large cavity structure inside it provides a larger space for absorbing and storing liquids.
[0012] The preparation method of the compressible expandable aerogel provided by the invention is simple to operate, the raw materials are cheap and readily available, and the aerogel is biodegradable and has high strength and liquid absorption performance, thus providing a low-cost, environmentally friendly, excellent new material for hemostatic materials and having high practical value.
[0013] Preferably, in S1, the mass ratio of sodium carboxymethyl cellulose to coniferous pulp is 4:1 to 2:1.
[0014] Coniferous pulp is a renewable resource with high strength and modulus, as well as good hygroscopicity and air permeability. The raw material cost is cheap and easy to obtain. When it is mixed with sodium carboxymethyl cellulose in the above-mentioned proportion, the prepared aerogel can have high overall strength, toughness and compression resilience.
[0015] Preferably, in S1, the mass concentration of sodium carboxymethyl cellulose in the mixed solution is 2% to 8%.
[0016] Preferably, in S2, the protonic acid is at least one of hydrochloric acid, sulfuric acid or phytic acid.
[0017] Preferably, the mass concentration of the protonic acid is 4% to 6%, and the volume mass ratio of the protonic acid to the mixed solution is (0.5 to 3) mL:10 g.
[0018] The preferred proton acid and the amount added can form a variety of cross-linking effects between the molecular chains in the aggregation area, inducing the molecular chains to form a more refined phase separation structure. At the same time, the hydrogen bonds and ion coordination bonds formed between the molecular chains have self-repairing properties. Under high loads, the hydrogel can be given recoverability and self-healing properties through breaking and reconstruction. At the same time, due to the formation of a more refined phase separation structure, the physical strength per unit area of the hydrogel is improved, and the skeleton and the pores, bonds or ion coordination bonds cooperate to disperse stress and dissipate energy, prevent crack propagation, and give the aerogel overall strength and toughness.
[0019] Preferably, in S2, the chemical cross-linking agent is one or both of an aqueous solution of epichlorohydrin or an aqueous solution of glutaraldehyde.
[0020] Preferably, the volume mass ratio of the chemical cross-linking agent to the mixed solution is (0.2-2) mL:10 g.
[0021] The preferred cross-linking agent and the amount of cross-linking agent added can promote the formation of multiple cross-links between sodium carboxymethyl cellulose and coniferous pulp fibers in the system, thereby improving the overall strength, toughness and resilience of the aerogel material.
[0022] Preferably, the mass concentration of the sodium dodecyl sulfate solution is 0.4% to 0.6%, and the volume mass ratio of the sodium dodecyl sulfate solution to the mixed solution is (0.2 to 2) mL:10 g.
[0023] By combining the foaming effect of sodium dodecyl sulfate with the ice template method, a three-dimensional large pore structure can be formed inside the aerogel, providing more space for absorbing and storing liquids and improving the liquid absorption rate.
[0024] Furthermore, S2 is preferably freeze-dried at -15°C for 28 hours.
[0025] Under the preferred freezing temperature and freezing time, ice crystal pores and polyelectrolyte molecular chain aggregation areas will be formed. In the molecular chain aggregation areas, the molecular chains are close to each other and form local entanglements. After the gel is melted, the system maintains a certain degree of pore morphology due to the local entanglement of the molecular chains, providing conditions for the formation of aerogels with three-dimensional large pore structures.
[0026] Preferably, in S3, the drying is freeze drying, the drying temperature is -40°C to -60°C, and the drying time is 20h to 24h.
[0027] The present invention also provides a compressible expandable aerogel, which is prepared by any of the above-mentioned methods for preparing a compressible expandable aerogel.
[0028] Furthermore, the compressible expandable aerogel has a pore size of 110 μm to 130 μm, a liquid adsorption rate of 20 g / g to 50 g / g, can be compressed to 2.5% to 10% of the original volume, has a deformation recovery capacity of no more than 20 seconds, and a tensile strength of ≥1.2 MPa.
[0029] The aerogel provided by the present invention has good compressibility, expandability and water absorption, and has good stability and biodegradability. It can be stably stored for more than 2 years in an air environment at room temperature, and can be completely degraded in the soil within 30 days after being thrown. It can be used as a medical hemostatic material, has the advantages of environmental protection, low energy consumption, degradability, low cost, etc., and shows high application potential in the field of environmentally friendly hemostatic materials.
[0030] The present invention also provides use of any of the above-mentioned compressible expandable aerogels in the preparation of hemostatic materials.
[0031] The aerogel material provided by the present invention can be compressed to 2.5% to 10% of its original volume, and can rapidly expand to 95% to 100% of its original volume within 20 seconds when in contact with water after compression, and has a liquid absorption rate of ≥20g / g, high overall strength and toughness, and no toxic organic solvents are used in the preparation process. The aerogel material is biodegradable, low-cost, suitable for large-scale production, and has broad application prospects in the field of hemostatic materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a SEM image of the compressible expandable aerogel prepared in Example 1 of the present invention;
[0033] Figure 2 This is a physical picture of the original length of the compressible expandable aerogel prepared in Example 1 after applying about 95% compression deformation upon contact with water;
[0034] Figure 3 The actual pictures before and after applying 90% compression deformation to the compressible expandable aerogel prepared in Example 1, (a) before compression, (b) after compression, (c) recovery after contact with water;
[0035] Figure 4 is a compressive stress-strain curve diagram of the compressible expandable aerogel prepared in Example 1 during the process of applying 90% of the compressive deformation amount;
[0036] Figure 5 The actual pictures are before and after the compressible expandable aerogel prepared in Example 1 was subjected to 3000 cycles of 90% compression deformation in water;
[0037] Figure 6 The degradation effect diagram of the compressible expandable aerogel prepared in Example 1 placed in moist soil at different times;
[0038] Figure 7 This is a tensile stress-strain curve of the compressible expandable aerogel prepared in Example 1. DETAILED DESCRIPTION
[0039] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0040] In order to better illustrate the present invention, further examples are given below.
[0041] Example 1
[0042] The present invention provides a method for preparing a compressible expandable aerogel, comprising the following steps:
[0043] 0.3 g of sodium carboxymethyl cellulose and 0.15 g of conifer pulp were added to deionized water to obtain 10 g of a mixed solution; 1 mL of 5% hydrochloric acid, 1 mL of 0.5% glutaraldehyde solution and 1 mL of 0.5% sodium dodecyl sulfate solution were added thereto, stirred for 30 minutes, frozen at -15°C for 28 hours, taken out, and residual acid, glutaraldehyde and sodium dodecyl sulfate were washed away with deionized water to obtain a hydrogel; the hydrogel was freeze-dried at -40°C for 24 hours to obtain a compressible expandable aerogel.
[0044] Performance Test:
[0045] The SEM image of the compressible expandable aerogel prepared in this example is as follows: Figure 1 As shown in the figure, a, b, and c are SEM images of compressible expandable aerogels at different magnifications. It can be seen that after the physical and chemical double crosslinking of sodium carboxymethyl cellulose and conifer pulp and the foaming pore-forming process, a three-dimensional microporous hole structure with a large pore size is formed, with a pore size of 110μm to 130μm, and the pore wall is a thin layer of porous fibrous structure rich in wood pulp fibers. This unique microfiber structure can be deformed synergistically, so that it can disperse stress and dissipate energy under multiple compression deformations, especially after absorbing liquid, it can expand rapidly and return to its original length.
[0046] The compressible expandable aerogel prepared in this embodiment is made into a cylindrical shape (height 6.4-6.5 cm). The cylindrical sample is axially compressed under extreme conditions, and a compression deformation of 97.5% is applied, that is, it is compressed to 1 / 40 of the original length, and then placed in deionized water. After contacting water, the compressed sample can quickly recover to its original length within 4 seconds.
[0047] The compressible expandable aerogel prepared in this embodiment is subjected to a compression deformation of about 95%, that is, compressed to about 1 / 20 of its original length, and then placed in deionized water. After contacting water, it can quickly recover its original length within 4 seconds. Figure 2 shown.
[0048] The compressible expandable aerogel prepared in this embodiment is made into a cylindrical shape with a length of 10 mm and a diameter of 11 mm. A 90% compression deformation is applied to the sample. After compression, it is placed in deionized water and can quickly recover to its original length within 3 seconds. Figure 3 The compressive stress-strain curve of the experimental process is shown in Figure 4 As shown, according to Figure 4 It can be concluded that when 90% of the compression deformation is applied, the compression stress is 2.052MPa, which proves that this material is easy to compress and convenient for production and use.
[0049] According to the above test, the compressible expandable aerogel was subjected to a 90% compression deformation, and then placed in deionized water for recovery. After repeated cycle tests for 3000 times, its length remained at 95% to 98% of its original length. The samples before and after the cycle tests were as follows: Figure 5 As shown, it is proved that the sample has excellent compression performance, absorption performance and expansion resilience performance.
[0050] The compressible expandable aerogel prepared in this example was cut into cylindrical samples with a diameter of 10 mm and a height of 5 mm, and placed in moist soil at 20°C for degradation test. In the 0-10 day stage, the degradation phenomenon was not obvious; in the 10-20 day stage, the degradation began to accelerate; in the 20-30 day stage, the degradation was completely achieved. The results are shown in FIG. Figure 6 shown.
[0051] The compressible expandable aerogel prepared in this example was cut into rectangular sample strips with a length of 30 mm, a width of 11 mm, and a thickness of 2 mm. The tensile strength was tested using a universal testing machine using GB / T 14344-2008 "Test method for tensile properties of chemical fiber filaments" at a tensile speed of 10 mm / min. The results are as follows: Figure 7 As shown in the figure, its tensile strength is 1.291MPa, which proves that it is an aerogel material with good tensile strength.
[0052] The sample prepared in this example was weighed and placed in deionized water, and allowed to stand for 10 minutes. The corners of the sample were clamped with tweezers, and its weight was measured when no liquid dripped. The liquid absorption rate was tested to be 25 g / g.
[0053] Example 2
[0054] The present invention provides a method for preparing a compressible expandable aerogel, comprising the following steps:
[0055] 0.4 g of sodium carboxymethyl cellulose and 0.1 g of conifer pulp were added to deionized water to obtain 10 g of a mixed solution; 0.5 mL of hydrochloric acid with a mass concentration of 6%, 0.2 mL of analytically pure epichlorohydrin and 0.2 mL of a sodium dodecyl sulfate solution with a mass concentration of 0.6% were added thereto, stirred for 30 minutes, frozen at -16°C for 25 hours, taken out, and residual acid, glutaraldehyde and sodium dodecyl sulfate were washed away with deionized water to obtain a hydrogel; the hydrogel was freeze-dried at -40°C for 24 hours to obtain a compressible expandable aerogel with a tensile strength of 1.187 MPa and a liquid absorption rate of 21 g / g.
[0056] Example 3
[0057] The present invention provides a method for preparing a compressible expandable aerogel, comprising the following steps:
[0058] 0.8 g of sodium carboxymethyl cellulose and 0.4 g of conifer pulp were added to deionized water to obtain 10 g of a mixed solution; 3 mL of 4% hydrochloric acid, 2 mL of 0.4% glutaraldehyde solution and 2 mL of 0.4% sodium dodecyl sulfate solution were added thereto, stirred for 30 min, frozen at -20°C for 24 h, taken out, and residual acid, glutaraldehyde and sodium dodecyl sulfate were washed away with deionized water to obtain a hydrogel; the hydrogel was freeze-dried at -40°C for 24 h to obtain a compressible expandable aerogel with a tensile strength of 2.031 MPa and a liquid absorption rate of 23 g / g.
[0059] Comparative Example 1
[0060] This comparative example provides a method for preparing a compressible expandable aerogel, which is different from Example 1 only in the freezing time, and comprises the following steps:
[0061] 0.3 g of sodium carboxymethyl cellulose and 0.15 g of conifer pulp were added to deionized water to obtain 10 g of a mixed solution; 1 mL of 5% hydrochloric acid, 1 mL of 0.5% glutaraldehyde solution and 1 mL of 0.5% sodium dodecyl sulfate solution were added thereto, stirred for 30 min, frozen at -15°C for 18 h, taken out, and the residual acid, glutaraldehyde and sodium dodecyl sulfate were washed away with deionized water to obtain a hydrogel; the hydrogel was freeze-dried at -40°C for 24 h to obtain a compressible expandable aerogel with a tensile strength of 0.764 MPa.
[0062] Comparative Example 2
[0063] This comparative example provides a method for preparing a compressible expandable aerogel, which is different from Example 1 only in that sodium carboxymethyl cellulose is replaced with an equal amount of hydroxypropyl cellulose, and specifically comprises the following steps:
[0064] 0.3 g of hydroxypropyl cellulose and 0.15 g of conifer pulp were added to deionized water to obtain 10 g of a mixed solution; 1 mL of 5% hydrochloric acid, 1 mL of 0.5% glutaraldehyde solution and 1 mL of 0.5% sodium dodecyl sulfate solution were added thereto, stirred for 30 min, frozen at -15°C for 28 h, taken out, and the residual acid, glutaraldehyde and sodium dodecyl sulfate were washed away with deionized water to obtain a hydrogel, which could not maintain a fixed shape; the hydrogel was freeze-dried at -40°C for 24 h to obtain a compressible expandable aerogel, which had an extremely irregular morphology compared with Example 1 and a tensile strength of only 0.203 MPa.
[0065] Comparative Example 3
[0066] This comparative example provides a method for preparing a compressible expandable aerogel, which is different from Example 1 only in that sodium carboxymethyl cellulose is replaced with an equal amount of chitosan, and specifically comprises the following steps:
[0067] 0.3 g of chitosan and 0.15 g of conifer pulp were added to a 0.1 mol / L acetic acid solution to obtain 10 g of a mixed solution; 1 mL of a 0.5% mass concentration of glutaraldehyde solution and 1 mL of a 0.5% mass concentration of sodium dodecyl sulfate solution were added thereto, stirred for 30 min, frozen at -15°C for 28 h, taken out, and the residual acid, glutaraldehyde and sodium dodecyl sulfate were washed away with deionized water to obtain a hydrogel; the hydrogel was freeze-dried at -40°C for 24 h to obtain a compressible expandable aerogel, which had a poorer morphology than that of Example 1, had more irregular holes on the surface, and the sample was more brittle and easily damaged, and was difficult to expand when exposed to water after compression.
[0068] Comparative Example 4
[0069] This comparative example provides a method for preparing a compressible expandable aerogel, which is different from Example 1 only in that sodium dodecyl sulfate is replaced with an equal amount of sodium citrate, and specifically comprises the following steps:
[0070] 0.3 g of sodium carboxymethyl cellulose and 0.15 g of conifer pulp are added to deionized water to obtain 10 g of a mixed solution; 1 mL of 5% hydrochloric acid, 1 mL of 0.5% glutaraldehyde solution and 1 mL of 0.5% sodium citrate solution are added thereto, stirred for 30 minutes, frozen at -15°C for 28 hours, taken out, and residual acid, glutaraldehyde and sodium dodecyl sulfate are washed away with deionized water to obtain a hydrogel; the hydrogel is freeze-dried at -40°C for 24 hours to obtain a compressible expandable aerogel with a liquid absorption rate of 15 g / g.
[0071] Comparative Example 5
[0072] This comparative example provides a method for preparing a compressible expandable aerogel, which is different from Example 1 only in that conifer pulp is not added, and comprises the following steps:
[0073] 0.3 g of sodium carboxymethyl cellulose was added to deionized water to obtain 10 g of a mixed solution; 1 mL of 5% hydrochloric acid, 1 mL of 0.5% glutaraldehyde solution and 1 mL of 0.5% sodium dodecyl sulfate solution were added thereto, stirred for 30 min, frozen at -15°C for 28 h, taken out, and the residual acid, glutaraldehyde and sodium dodecyl sulfate were washed away with deionized water to obtain a hydrogel; the hydrogel was freeze-dried at -40°C for 24 h to obtain a compressible expandable aerogel with a tensile strength of only 0.425 MPa.
[0074] Comparative Example 6
[0075] This comparative example provides a method for preparing a compressible expandable aerogel, which is different from Example 1 only in that coniferous pulp is replaced by broadleaf pulp, and specifically comprises the following steps:
[0076] 0.3 g of sodium carboxymethyl cellulose and 0.15 g of broadleaf pulp were added to deionized water to obtain 10 g of a mixed solution; 1 mL of 5% hydrochloric acid, 1 mL of 0.5% glutaraldehyde solution and 1 mL of 0.5% sodium dodecyl sulfate solution were added thereto, stirred for 30 min, frozen at -15°C for 28 h, taken out, and the residual acid, glutaraldehyde and sodium dodecyl sulfate were washed away with deionized water to obtain a hydrogel; the hydrogel was freeze-dried at -40°C for 24 h to obtain a compressible expandable aerogel with a tensile strength of only 0.645 MPa.
[0077] In summary, the embodiment of the present invention prepares an aerogel with good compression performance and water rebound performance based on sodium carboxymethyl cellulose and coniferous pulp. The aerogel has a high liquid absorption rate (≥20g / g), high overall strength and toughness, and the preparation method is simple. The raw materials are cheap and easily available. It provides a new environmentally friendly and degradable material for hemostatic materials and has high practical value.
[0078] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a compressible expandable aerogel, characterized in that: The steps include: S1, adding sodium carboxymethyl cellulose and conifer pulp into water and mixing them evenly to obtain a mixed solution; S2, adding protonic acid, chemical crosslinking agent and sodium dodecyl sulfate solution to the mixed solution, mixing evenly, and freezing to obtain a hydrogel; wherein the freezing is performed at a temperature below -15°C for more than 24 hours or at a temperature below -196°C in liquid nitrogen for more than 2 hours; S3, washing the hydrogel in water, and drying the hydrogel to obtain a compressible and expandable aerogel.
2. The method for preparing the compressible expandable aerogel according to claim 1, characterized in that: In S1, the mass ratio of sodium carboxymethyl cellulose to coniferous pulp is 4:1 to 2:
1.
3. The method for preparing the compressible expandable aerogel according to claim 2, characterized in that: In S1, the mass concentration of sodium carboxymethyl cellulose in the mixed solution is 2% to 8%.
4. The method for preparing the compressible expandable aerogel according to claim 1, characterized in that: In S2, the protonic acid is at least one of hydrochloric acid, sulfuric acid or phytic acid; and / or In S2, the chemical cross-linking agent is one or both of an aqueous solution of epichlorohydrin or an aqueous solution of glutaraldehyde.
5. The method for preparing the compressible expandable aerogel according to claim 4, characterized in that: The mass concentration of the protonic acid is 4% to 6%, and the volume mass ratio of the protonic acid to the mixed solution is (0.5 to 3) mL:10 g; and / or The volume mass ratio of the chemical cross-linking agent to the mixed solution is (0.2-2) mL:10 g.
6. The method for preparing the compressible expandable aerogel according to claim 1, characterized in that: The mass concentration of the sodium dodecyl sulfate solution is 0.4% to 0.6%, and the volume mass ratio of the sodium dodecyl sulfate solution to the mixed solution is (0.2 to 2) mL:10 g.
7. The method for preparing the compressible expandable aerogel according to claim 1, characterized in that: In S3, the drying is freeze drying, the drying temperature is -40°C to -60°C, and the drying time is 20h to 24h.
8. A compressible expandable aerogel, characterized in that: The compressible expandable aerogel is prepared by the preparation method of any one of claims 1 to 7.
9. The compressible expandable aerogel according to claim 8, characterized in that: The compressible expandable aerogel has a pore size of 110 μm to 130 μm, a liquid adsorption rate of 20 g / g to 50 g / g, can be compressed to 2.5% to 10% of the original volume, has a deformation recovery capacity of no more than 20 seconds, and a tensile strength of ≥1.2 MPa.
10. Use of the compressible expandable aerogel according to claim 8 or 9 in preparing hemostatic materials.